The Role of Investigators in Collecting Evidence Using Sniffer Dogs (K9) Against Narcotics Crimes - Amrullah, Rinaldy; Sihite, Nurul Riskia Safitri (Universitas Lampung, 2023)
The use of sniffer dogs (K9) to assist police in collecting evidence related to narcotics crimes is grounded in the principle that investigators are permitted to employ all lawful means in the pursuit of their duties to uncover criminal offenses. This research adopts both normative and empirical juridical approaches, revealing that the role of investigators in utilizing K9 units encompasses normative, ideal, and factual dimensions. However, several factors inhibit investigators from effectively executing their roles in this capacity, notably the limited regulatory framework governing the use of sniffer dogs, which is confined to the Decree of the National Police Chief No. Pol: SKEP/251/IV/2004 and No. Pol: SKEP17/X/2011. There is a pressing need for a comprehensive legal basis that explicitly regulates the validity and utilization of these laws. Furthermore, challenges related to law enforcement personnel are significant, particularly the shortage of police officers trained as K9 handlers at Polda Lampung. Infrastructural issues, including suboptimal health management of the K9 units, particularly the sniffer dogs, also hinder effective operations. Addressing these factors is crucial for enhancing the role of K9 units in narcotics investigations.